(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article deals with the fact that the Sri Lankan Tamils reached India as refugees after the ethnic problem of 1983, and as per the United Nations High Commission for Refugees conditions, the government of India and the government of Tamil Nadu treated them. The refugees were given housing and a monthly stipend to help them support their families.